Comparative Study of Quality of Life among Epileptic and Hypertensive Patients - Maharjan, Laxman; Dahal, Prasanna; Dahal, Bibek; Bhattarai, Choodamani (Sunsari Technical College Journal, 2016)
A prospective cross-sectional study was conducted through patient reported outcomes of the therapy in epileptic and hypertensive patients for the period of two months at B.P.Koirala Institute of Health Sciences, Hospital, Dharan. 52 epileptic and 60 hypertensive patients were analyzed with mean±SD ages 23.69±7.61 and 60.68±14.34 years old respectively. Out of which 53.85% and 46.66% were male in epilepsy and hypertension respectively. The Mean±SD (HRQOL) 60±17 was found in epilepsy and 59±6 in hypertension. Social function, scored 61 out of 100, was highly reduced in epilepsy than in hypertension whereas role limitation due to physical function is comparatively reduced in hypertension than epilepsy, although there were no significant difference between mean HRQOL of epilepsy and hypertension (P>0.05) with correlation -0.084 in paired samples T-test. There were no variations in HRQOL by gender in both groups after having drug therapy in both categories. Independent sample T test (P>0.025) showed that there were no significant differences in mean HRQOL and every domains of HRQOL of epilepsy with cut point 20 years. But physical functioning, energy level and general health were significantly (P<0.035) different in between age group ≥ 50 and < 50 years with hypertension. The study concluded that the Health Related Quality Of Life is low in both epilepsy and hypertension than general population regardless gender and age. In hypertension a decrease in QOL was observed with age, only in relation to physical and psychological health rather than other health domains but in epilepsy there were no significant variation in health domains of HRQOL by gender and age. Sunsari Technical College Journal 2015, 2(1):27-32